Study on the Removal of Copper Ion (Cu2+) From Industrial Wastewater by Using Ion Exchange Technique - Muhammad Taufiq bin Roslan, Muhammad Taufiq (2011)
The aim of this study is to determine the optimum condition for copper (II) ion removal from industrial wastewater based on certain criteria; effect of resin dose, initial metal concentration, and pH.